Effect of FinTech on cash holding: Quarterly evidence from Nigeria - Samuel, Udo Emmanuel; Prince, Abner Ishaku; Ndubuaku, Victor; Udoh, Ben Etim; Okoh, Johnson I (The Economics and Finance Letters, 2023)
The operational activities of FinTech (Financial technology) have restyled the operational functionalities of the classical financial system in terms of cash holding. The purpose of this study is to scrutinize FinTech’s effect on cash holdings in Nigeria. Using quarterly data collated from the Central Bank of Nigeria from 2009 Q1-2020 Q4. The cointegrating nexus was estimated using the autoregressive distributed lag/bounds test model (ARDL) and the error correction model (ECM) approach. The Phillips-Perron unit root test was adopted to determine the stationarity properties of the series and their order of integration. Empirical results show the existence of a positive long run nexus between FinTech indicators of mobile banking (MOB), point of sales (POSs), Internet banking (INB), automated teller machine (ATM), and cash holding within the quarterly period under consideration. The ECM results of the short-run divergent factors of economic and financial vagueness, poverty, and literacy, among others, structural and institutional factors influencing the dogged cash transactions in Nigeria, converge back to equilibrium at 90% for ATM, 58% for POS, MOB at 67%, and WEB at 64%, respectively. This study expands its frontiers to accommodate exchange and interest rates as vital determinants of cash holding. The ARDL result offers a varied empirical perspective in contrast to the predominantly employed classical linear regression. Given the statistical limitations associated with findings derived from a singular model, it is imperative for regulators to possess a comprehensive comprehension of the operational mechanisms of Financial Technology (FinTech). This understanding would enable them to formulate appropriate policies that foster the adoption and utilization of FinTech platforms.